2013
DOI: 10.1136/bjsports-2012-091826
|View full text |Cite
|
Sign up to set email alerts
|

Would they dope? Revisiting the Goldman dilemma

Abstract: Goldman's results do not match our sample. A subset of athletes is willing to dope and another subset is willing to sacrifice their life to achieve success, although to a much lesser degree than that observed by Goldman. A larger scale online survey is now viable to answer important questions such as variation across sports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 28 publications
0
15
0
5
Order By: Relevance
“…Goldman et al's research demonstrates that highly competitive athletes willingly take significant risks with their health in their pursuit of athletic goals. In sharp contrast to the findings of Goldman et al, a recent study by other authors [3] found that only two athletes out of 212 male and female athletes would accept this 'Faustian' option. The authors hypothesized that changes in the social and political context have reduced the risk athletes are willing to take for victory and that the Goldman et al dilemma is no longer relevant.…”
Section: Introductionmentioning
confidence: 52%
“…Goldman et al's research demonstrates that highly competitive athletes willingly take significant risks with their health in their pursuit of athletic goals. In sharp contrast to the findings of Goldman et al, a recent study by other authors [3] found that only two athletes out of 212 male and female athletes would accept this 'Faustian' option. The authors hypothesized that changes in the social and political context have reduced the risk athletes are willing to take for victory and that the Goldman et al dilemma is no longer relevant.…”
Section: Introductionmentioning
confidence: 52%
“…This is not least discouraging since the only study that have tried to replicate the Mirkin/Goldman survey in a scientific manner has found the complete opposite conclusion: very few athletes are willing to die for a medal. Indeed, athletes' psychological constitution is in this respect similar to that found in the general population (Connor & Mazanov, 2009;Connor, Woolf, & Mazanov, 2013). Although without the requisite methodology, the findings of Mirkin/Goldman are apparently too good not to be mentioned.…”
Section: Scientism and The Culture Of Sciencementioning
confidence: 69%
“…En este tipo de validez no se recurre a un criterio estadístico, sino a uno de basado en la justificación del contenido del cuestionario para que se ajuste a la realidad que pretende estudiar. Se estableció de acuerdo con tres aspectos: a) la lógica interna del cuestionario mediante la estructuración del mismo en las diferentes dimensiones de estudio; b) la representatividad conceptual de estas dimensiones tomando como referente para su elaboración estudios sobre opinión y actitud ante el dopaje (Connor et al, 2013;Mroczkowska, 2011;Whitaker et al, 2012), y c) la posterior revisión del cuestionario a través de un juicio de expertos en el que participaron tres profesores titulares de universidad ajenos al proyecto y que dieron su aprobación a la versión final del cuestionario.…”
Section: Instrumento Y Procedimiento De Recogida De Datosunclassified
“…Aunque con distinta proporcionalidad, sus resultados coinciden en mostrar un desacuerdo mayoritario hacia la legalización del dopaje en el deporte. En cuanto a los motivos que conducirían a doparse, el más importante sería ganar las competiciones y mejorar el rendimiento deportivo (Connor et al, 2013;Mroczkowska, 2011;Scarpino et al, 1990;Striegel et al, 2002). Otros estudios señalan que en la conducta dopante también influyen: la percepción de que el resto de competidores se dope (Dunn et al, 2012; Morente-Sánchez y Zabala, 2013); una mayor orientación hacia el ego que hacia la tarea a la hora de competir (Sas-Nowosielski y Swiatkowska, 2008); no ver mal el saltarse las reglas (Whitaker et al, 2012), o el hecho de estar a favor de la legalización del dopaje (Kindlundh et al, 1998;Petróczi, 2007).…”
Section: Introductionunclassified